2019
DOI: 10.3758/s13428-019-01213-5
|View full text |Cite
|
Sign up to set email alerts
|

The SNARC and MARC effects measured online: Large-scale assessment methods in flexible cognitive effects

Abstract: The Spatial-Numerical Association of Response Codes (SNARC) effect (i.e., faster reactions to small/large numbers on the left-/ right-hand side) is usually observed along with the linguistic Markedness of Response Codes (MARC) effect-that is, faster left-/ right-hand responses to odd/even numbers. The SNARC effect is one of the most thoroughly investigated phenomena in numerical cognition. However, almost all SNARC and MARC studies to date were conducted with sample sizes smaller than 100. Here we report on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(108 citation statements)
references
References 71 publications
9
98
1
Order By: Relevance
“…The SNARC effect has not only been replicated in many studies using parity judgment (see Cipora, Soltanlou, Reips, & Nuerk, 2019 for a large-scale online replication). It has also been reported in various other numerical tasks in both typical and atypical populations across various developmental stages (for reviews see Fischer Toomarian & Hubbard, 2018;Wood, Willmes, Nuerk, & Fischer, 2008 for a metaanalysis), generally highlighting robustness of the effect.…”
Section: Taking the Snarc Effect As An Examplementioning
confidence: 99%
“…The SNARC effect has not only been replicated in many studies using parity judgment (see Cipora, Soltanlou, Reips, & Nuerk, 2019 for a large-scale online replication). It has also been reported in various other numerical tasks in both typical and atypical populations across various developmental stages (for reviews see Fischer Toomarian & Hubbard, 2018;Wood, Willmes, Nuerk, & Fischer, 2008 for a metaanalysis), generally highlighting robustness of the effect.…”
Section: Taking the Snarc Effect As An Examplementioning
confidence: 99%
“…In several studies gender differences have been observed in some spatial representations of number (e.g., Bull et al, 2013;Reinert et al, 2017), in children's early arithmetic skill (Krinzinger et al, 2012;Hornburg et al, 2017;see also Brunner et al, 2011), and even in adults' arithmetic and numerical skills (Pletzer et al, 2013(Pletzer et al, , 2016. However, many recent studies have not found that females and males differ, for example, in a meta-analysis of math performance (Hyde, 2016), in several studies on children at various stages of their development (Morsanyi et al, 2018;Bakker et al, 2019;Hutchison et al, 2019); and in an adult online study testing the SNARC effect with over 1000 participants (see supplementary materials of Cipora et al, 2019). Because of these diverging results in the literature, which may differ depending on task, sample, culture and paradigm, we included gender as a predictor to examine whether it has any effect on embodied learning of basic numerical skills.…”
Section: Introductionmentioning
confidence: 99%
“…Even though magnitude is response-irrelevant, it influences the reaction time pattern. The SNARC effect is very robust and has been replicated multiple times 21 , including in a large-scale online setup 22 . It was also observed with several modifications to the original bimanual parity setup 23 .…”
Section: The Snarc Effectmentioning
confidence: 99%
“…For children a better level of math skills was related to a stronger SNARC effect, whereas for adults better math skills were related to a weaker SNARC effect. 20 Fischer & Rottmann, 2005 42 Bonato et al, 2007 43 Bull et al, 2013 44 Cipora & Nuerk, 2013 32 Göbel et al, 2015 45 Cipora et al, 2019 22 Toomarian et al, 2019 46 Special groups -high math skills level He et al, 2019 47 Cipora et al, 2016 48 -Note that brain lesioned patients or individuals with genetic disorders are not considered. Studies with significant effects are in bold font.…”
Section: The Snarc Effect and Math Skill Level -What We Learned In Thmentioning
confidence: 99%
See 1 more Smart Citation